The Political Consequences of Be(com)ing Mindful. How Mindfulness Might Affect Political Attitudes - Ramstetter, Lena (Frontiers in Political Science, 2021)
Though research provides ample evidence that mindfulness shapes psychological processes and states that are linked to political attitudes and behavior, political science has so far largely ignored mindfulness as a potential explanatory factor shaping political attitudes and actions. This literature review aims to provide a comprehensive overview of the concept of mindfulness and at outlining potential linkages between mindfulness and political attitudes. I begin by identifying gaps in the literature on political attitude formation and change as well as its linkage to political behavior. I then introduce mindfulness as a multifaceted concept, discussing its definitional features and unravelling the mechanisms of mindfulness affecting cognitive and emotional abilities. Building on this foundation, I review research on correlates and effects of mindfulness on attitudes and behaviors related to the political domain, such as pro-environmentalism and pro-social behavior. Critically reflecting on extant research on mindfulness, I propose possible research avenues for political science that enhance dialogue with neuroscience and social psychology.